Scanner and kVp dependence of measured CT numbers in the ACR CT phantom. (4th November 2013) - Cropp, Robert J.; Seslija, Petar; Tso, David; Thakur, Yogesh
Abstract : Quality control testing of CT scanners in our region includes a measurement of CT numbers in the American College of Radiology (ACR) CT phantom using a standardized protocol. CT number values are clinically relevant in determining the composition of various tissues in the body. Accuracy is important in the characterization of tumors, assessment of coronary calcium, and identification of urinary stone composition. Effective quality control requires that tolerance ranges of CT number values be defined: a measured value outside the range indicates the need for further investigation and possible recalibration of the scanner. This paper presents the results of CT number measurements on 36 scanners (25 GE, 10 Siemens and 1 Toshiba) at each available kVp. Among the five materials (solid water, air, polyethylene, acrylic, bone‐equivalent) the measured CT numbers exhibit manufacturer and kVp dependence, which should be taken into account when defining tolerances. With this scan protocol, air and solid water values are significantly higher on GE scanners than on Siemens scanners ( p ‐ value < 0.01 at each kVp). The CT numbers of polyethylene and acrylic increase with kVp, while the bone‐equivalent CT number decreases. These results are used to define manufacturer‐ and kVp‐specific tolerance ranges for the CT numbers of each material in this phantom, which will be used in our quality control program. PACS numbers: 87.57.qp, 87.57.C‐